Pola dan Dampak Mobilitas Petani menjadi Tukang Becak di Kecamatan Purworejo - Dwiningtyas Padmaningrum; Emi Widiyanti (Universitas Sebelas Maret, 2004)
The population mobility happened if there are difference value between urban and rural specially at the economic and opportunity of job aspect. The pattern of population mobility: permanent and non-permanent (circulair and commuting). Mobility pattern of responder in this research entirely represent non permanent mobility, consisting of mobility commute (63,3 percent) and also circulair mobility (36,7 percent). As for decision to do mobility because invited by their friend or family and also coincidence of this work is can access. This mobility affect positive to responder, social and also economics.